Dampak Pelanggaran Hukum Terhadap Lingkungan(Studi Kasus Pembuangan Sampah Liar Di Kota Batam) - Seli Fila Dwi Pratika; Muhammad Fajar Hidayat (CV. ITTC INDONESIA, 2024)
Violations of the law are actions that violate laws and regulations, policies and other actions that indicate corruption, collusion and nepotism within the Coordinating Ministry for Maritime Affairs and Investment. Violations of the law can be committed by anyone, including students, and can take various forms, from the lightest to the most serious. The law regulates people's behavior by determining what actions are prohibited and regulating the sanctions that can be imposed on perpetrators of violations. This research uses an empirical juridical approach, where this approach examines applicable legal provisions and what happens in reality in society. This research analyzes the impact of law violations on the environment, analyzing cases of illegal waste dumping in Batam City. The main legal basis that regulates this is Batam City Regional Regulation Number 11 of 2013 concerning waste management, and article 69 paragraph 1 which regulates sanctions for violations of illegal waste disposal in Batam City.